Electric vehicles in Bangladesh: Impact on the environment, mobility, and the economy of an impending ban - Syeda Nurunnahar; Md Shariful Islam; Mahbubur Rahman (Public Health Challenges, 2022)
Abstract The government of Bangladesh recently decided to outlaw electric three‐wheelers due to the rise in accidents on highways. Although the restriction is intended to improve road and transportation safety, it will only exacerbate the current economic crisis if alternate sources of income are not made available. Additionally, the use of battery‐powered electric three‐wheelers is significant for providing short‐distance transportation in rural areas and the commercial centers of metropolitan cities. In many villages, electric three‐wheelers are the only accessible mode of rapid transportation. Moreover, electric vehicles are environmentally beneficial because their increased use will lower the consumption of fossil fuels and CO2 emissions from the transportation sector. Banning electric three‐wheelers will have serious consequences for the environment, mobility, and the economy. Instead, the government can bring existing three‐wheeled motorized vehicles under Bangladesh Road Transport Authority supervision. Monitoring and policy making are easy when a mode of transport belongs to the formal sector. Adding necessary measures to use of the vehicle will boost mobility and save Bangladesh's environment and economy.